Fluoxetine Inhibits Canonical Wnt Signaling to Impair Embryoid Body Morphogenesis: Potential Teratogenic Mechanisms of a Commonly Used Antidepressant. (8th June 2018) - Warkus, Erica L L; Marikawa, Yusuke
Abstract: Fluoxetine is one of the most commonly prescribed antidepressants in the selective serotonin reuptake inhibitor (SSRI) class. Epidemiologic studies have suggested a link between maternal fluoxetine use during pregnancy and an increased incidence of birth defects. However, the mechanisms by which fluoxetine adversely impacts embryonic developments are unknown. Here, we used the mouse P19C5 embryoid body (EB) as a 3D morphogenesis model to investigate the developmental toxicity of fluoxetine. Morphological and molecular changes in P19C5 EBs replicate the processes of axial elongation and patterning seen in early embryos, and these changes are specifically and sensitively altered by exposure to developmental toxicants. Treatment with fluoxetine, or its major metabolite, norfluoxetine, adversely affected EB morphogenesis at concentrations of 6 µM and above. Treatment with other serotonin reuptake inhibitors or serotonin itself did not impair EB morphogenesis, suggesting that the adverse effects of fluoxetine are independent of serotonin signaling. Gene expression analyses showed that various key developmental regulators were affected by fluoxetine, particularly those involved in mesodermal differentiation. Reporter assays demonstrated that fluoxetine inhibited canonical Wnt signaling, and that the pharmacologic activation of canonical Wnt signaling partially alleviated the morphogenetic effects of fluoxetine. Fluoxetine also exhibited cytostatic effects independently of inhibition of the serotonin transporter or canonical Wnt signaling. These results suggest that the SSRI-independent actions of fluoxetine, namely inhibition of canonical Wnt signaling and reduction of cellular proliferation, are largely responsible for the observed adverse morphogenetic impacts. This study provides mechanistic insight for further investigations on the teratogenicity of fluoxetine.